Neuroprotective effects of targeting BET proteins for degradation with dBET1 in aged mice subjected to ischemic stroke. (July 2019) - DeMars, Kelly M.; Yang, Changjun; Candelario-Jalil, Eduardo
Abstract: Neuroinflammation after stroke significantly contributes to neuronal cell death. Bromodomain and Extra Terminal Domain (BET) proteins are essential to inflammatory gene transcription. BET proteins (BRD2, BRD3, BRD4, and BRDT) have varied effects including chromatin remodeling, histone acetyltransferase activity, and as scaffolds to recruit transcription factors; they couple chromatin remodeling with transcription. BRD2/4 are of particularly interest to stroke-induced neuroinflammation that contributes to delayed cell death as they are required for NF-κB-dependent gene transcription. We hypothesized that targeting BET proteins for degradation with dBET1, a proteolysis targeting chimera (PROTAC) that combines the highly selective BET inhibitor JQ1 and a ligand for cereblon E3 ubiquitin ligase, will reduce brain injury in ischemic stroke. Male aged mice (18–20 months old) were subjected to permanent occlusion of the middle cerebral artery and received either vehicle or dBET1 (10 mg/kg; i.p.) at various times after stroke. Neurobehavioral tests were performed before (baseline) and at 24 and 48 h after stroke induction. Infarct volume was quantified at 48 h. Data showed that BET degradation significantly reduced infarct volume in permanent focal cerebral ischemia in aged mice, and this was associated with reduced brain levels of pro-inflammatory mediators including TNF-α, CXCL1, CXCL10, CCL2, and matrix metalloproteinase-9. Treatment with dBET1 significantly reduced blood-brain barrier damage and infiltration of neutrophils into the ischemic brain. Importantly, treatment with the BET degrader dBET1 resulted in a significant improvement in stroke-induced neurological deficits. Collectively, these data indicate that BET proteins are a novel target for neuroprotection in ischemic stroke. Highlights: dBET1, a proteolysis targeting chimera, degrades BET protein BRD4 in the brain. Treatment with dBET1 reduces infarct volume in aged mice subjected to permanent focal cerebral ischemia. dBET1 reduces stroke-induced expression of pro-inflammatory mediators. BET blockade prevents blood-brain barrier damage and reduces neutrophil infiltration after stroke. dBET1 improves sensorimotor related neurological deficits after stroke in aged mice.